Expression of Putative Defense Responses in Cannabis Primed by Pseudomonas and/or Bacillus Strains and Infected by Botrytis cinerea - Balthazar, Carole; Cantin, Gabrielle; Novinscak, Amy; Joly, David L.; Filion, Martin (Frontiers in Plant Science, 2020)
Cannabis (Cannabis sativa L.) offers many industrial, agricultural, and medicinal applications, but is commonly threatened by the gray mold disease caused by the fungus Botrytis cinerea. With few effective control measures currently available, the use of beneficial rhizobacteria represents a promising biocontrol avenue for cannabis. To counter disease development, plants rely on a complex network of inducible defense pathways, allowing them to respond locally and systemically to pathogens attacks. In this study, we present the first attempt to control gray mold in cannabis using beneficial rhizobacteria, and the first investigation of cannabis defense responses at the molecular level. Four promising Pseudomonas (LBUM223 and WCS417r) and Bacillus strains (LBUM279 and LBUM979) were applied as single or combined root treatments to cannabis seedlings, which were subsequently infected by B. cinerea. Symptoms were recorded and the expression of eight putative defense genes was monitored in leaves by reverse transcription quantitative polymerase chain reaction. The rhizobacteria did not significantly control gray mold and all infected leaves were necrotic after a week, regardless of the treatment. Similarly, no systemic activation of putative cannabis defense genes was reported, neither triggered by the pathogen nor by the rhizobacteria. However, this work identified five putative defense genes (ERF1, HEL, PAL, PR1 and PR2) that were strongly and sustainably induced locally at B. cinerea’s infection sites, as well as two stably expressed reference genes (TIP41 and APT1) in cannabis. These markers will be useful in future researches exploring cannabis defense pathways.